Growth kinetics, purification and characterization of α-amylase produced from Bacillus licheniformis DSM-1969 using lignocellulosic banana waste as an elicitor - Bashir, Rashida; Syed, Quratulain; Mumtaz, Muhammad Waseem; Anwar, Farooq; Saari, Nazamid; Adnan, Ahmad (College of Natural Resources, North Carolina State University, 2014)
In this study, banana waste was used to investigate its elicitation potential for induced production of α-amylase from Bacillus licheniformis DSM-1969. Initially, six different media were investigated to select the composition with optimal yield. A comparison of the fermentations in the stirred fermenter or shake flasks revealed that B. licheniformis DSM-1969 was more active to synthesize α-amylase in the fermenter as compared to the shake flask. In the shake flask during the exponential phase, the specific growth rate, generation time, and number of generations were 0.19 h-1, 3.48 h-1, and 5.16 h-1, respectively, whereas in the stirred fermenter the above values were 0.3 h-1, 2.31 h-1 and 5.21 h-1, respectively. A significant difference was recorded in the specific substrate uptake rate and biomass growth yield during the exponential phase in the stirred fermenter in comparison to the shake flask. The enzyme was purified by ion-exchange chromatography using fast protein liquid chromatography (FPLC). α-amylase was purified 3.9 fold with a specific activity of 38.8 U/mg and molecular weight of 62 kDa. Characterization revealed that purified α-amylase remained stable over a broad pH and temperature range as compared to the crude enzyme. Activity of this novel extra thermo-stable α-amylase was stimulated to variable extents by Zn2+, Co2+, and Mn2+, whereas EDTA and Hg2+ showed inhibitory effects.